Formulation of carbamazepine and sodium valproate fixed dose combination for management of epilepsy - Seabi, Mmakgomo Eunice (My University, 2019)
Epilepsy is the fourth most common neurological disorder after migraine, stroke and Alzheimer’s disease and it affects about fifty million people worldwide. Careful consideration should be taken when deciding to initiate treatment in epilepsy as it should consider the balance between the possibility of further seizures and their associated risks, including the possible risk of sudden expected death, inconvenience and the risks of taking regular medication for each individual. In the early 1980’s, the first-line treatment for epilepsy was polytherapy. This was due to findings that smaller doses of two drugs rather than larger doses of one drug can achieve synergistic effects or less drug toxicity. However, following more trials on the treatment of epilepsy, this was later changed to monotherapy as first-line treatment. Despite the change, patients remain uncontrolled on a single anti-epileptic drug, thus they are initiated on polytherapy, one such combination being carbamazepine in combination with sodium valproate. The use of these in combination has pharmacological threats such as compliance, the control of side effects and the achievement of synergistic effects. The development of a Fixed Dose Combination (FDC) has often been used to resolve pharmacological threats, and this study aims to develop a fixed dose combination tablet of carbamazepine and sodium valproate to resolve the pharmacological threats in epilepsy. Samples of carbamazepine and sodium valproate and a physical mixture (1:1 w/w) of both drugs and excipients were prepared for compatibility with thermal analysis and spectroscopy techniques. Data was analysed by comparing the DSC curves, FTIR spectra, XRPD peaks and TAM analysis of carbamazepine and sodium valproate alone and in their physical mixture (1:1 w/w) and with excipients. Both carbamazepine and sodium valproate were evaluated for flowability using angle of repose, tapped and bulk density, compressibility index and particle size distribution. To formulate the proposed FDC tablet of carbamazepine and sodium valproate, direct compression and wet granulation methods were employed. The tablets were then evaluated for official and non-official post formulation parameters (weight variation, crushing strength, friability, diameter and thickness, and disintegration) according to BP and USP standards. A standardised HPLC method was developed and validated for analytical procedures. Dissolution studies were conducted xiii according to USP methods to verify and quantify the release of the APIs from the FDC tablet. Carbamazepine and sodium valproate were tested for compatibility with excipients using DSC, FTIR, XRPD and TAM analysis. The overall results confirmed that carbamazepine and sodium valproate are compatible, with each other and the excipients used in the study. Powder flow of carbamazepine and sodium valproate was poor, hence they were subjected to granulation prior to compression to improve flowability. The specifications of the fixed-dose combination were developed in accordance with the FDA’s quality by design concept and WHO recommendations. The tablets were subjected to non-official and official pharmacopoeial tests, and passed all the tests. Dissolution studies according to a USP method were conducted to verify and quantify the release of the APIs in the fixed-dose combination. The initial dissolution rate (DRi) of carbamazepine and sodium valproate in the SLS dissolution medium was rapid as required for an immediate release formulation. The study aimed at developing a fixed dose combination of carbamazepine and sodium valproate to try to reduce the burden of taking more than one tablet for epilepsy. Based on the results obtained from preformulation studies to assay of the final product, the study was successful.
Thesis ((M. Pharm. (Pharmaceutics)) -- University of Limpopo, 2019
Keywords: Fixed dose combination; carbamazepine; sodium valproate; Epilepsy; Compatibility; Epilepsy - Alternative treatment; Cerebrovascular disease in children